PENGARUH EKSTRAK DAUN JABON, MAHONI DAN CEMPAKA TERHADAP PERKECAMBAHAN BENIH JAGUNG DAN KACANG TANAH - Yanto Dolame; Maria Y.M.A. Sumakud; Semuel P. Ratag (COCOS, 2016)
ABSTRACTIn land-use commodities usually done by planting peanuts and corn along the tree, needs assessment of the impact of residues from tree Jabon, Mahogany and Cempaka. The research was conducted during the first week in November-December 2015. Every treatment gets 5 replications. Measurements alelopati influence on sprouts peanuts and corn were analyzed using analysis of variance (ANOVA). Leaf Extract Jabon, Mahogany and Cempaka alelopati shows that the effect does not interfere with the growth of sprouts in peanut seeds and corn. Keywords: Leaf extract, Allelopatih, Sprouts.